Perspective of polymeric films use for treatment of urogenital system inflammatory diseases in women - T. M. Litvinenko (Zaporožskij Medicinskij Žurnal)
At present treatment of bacterial vaginosis has the great importance in gynaecological practice. Development of vaginal films with Chinosol will allow to widen assortment of medications for therapy of this pathology.